Design and Development of a Device (Sifilotto®) for Tumour Tracking in Cervical Cancer Patients Undergoing Robotic Arm LINAC Stereotactic Body Radiation Therapy Boost: Background to the STARBACS Study - Silvana Parisi; Giacomo Ferrantelli; Anna Santacaterina; Elvio Grazioso Russi; Federico Chillari; Claudio Napoli; Anna Brogna; Carmelo Siragusa; Miriam Sciacca; Antonio Pontoriero; Giuseppe Iatì; Stefano Pergolizzi (Current Oncology, 2025)
Standard of Care (SOC) for locally advanced cervical cancer is represented by external beam radiation therapy concurrent with platinum-based chemotherapy and immunotherapy (cCIRT) followed by brachytherapy boost and immunotherapy maintenance. In some instances, it is impossible to perform brachytherapy due to patient and/or cancer issues. In these circumstances, an external beam boost could be delivered. Using a robotic arm LINAC, it is mandatory to use intramucosal implanted fiducials which are needed for tumour tracking. To avoid invasive procedures, we developed an original intravaginal 3D-printed universal device containing gold fiducials embedded within it. In this paper, we describe the step-by-step procedure that allowed us to obtain the utility model patent, including the in vivo test (feasibility, reproducibility, device compliance) on seven patients within the study protocol “STereotActic Radiotherapy Boost in locally Advanced Cervical carcinoma patientS” (STARBACS).